Rosabeth Moss Kanter on the frontiers of management - Kanter, Rosabeth Moss (Harvard Business School Press, 1997)
Contents: Leading Change: Innovation and Transformation; Managing People: Motivating, Empowering, Rewarding; Crossing Boundaries: Business and Its Partners; Values and Purpose: The Meaning Behind Management